Analysis Of Factors Related To The Cause Of Drug Withdrawal In Patients With Type Ii Diabetes Mellitus At Tk Ii Putri Hijau Kesdam 1/Bb Medan Hospital In 2020 - Eva Sartika Dasopang; Salmah Handayani Lubis; Fenny Hasanah; Nadia Nuzulia; Annisa Almunadia (International Journal of Health and Pharmaceutical (IJHP), 2024)
Diabetes Mellitus is a disease that cannot be cured and can only be controlled by taking medication regularly. Diabetes must be treated quickly and appropriately to get a cure. Taking drugs continuously can cause a person to start to feel bored to take drugs, causing a person to stop taking drugs. The purpose of this study was to provide information on the causes of drug withdrawal of patients with type II diabetes mellitus in the outpatient installation of Putri Hijau Medan Hospital. This research is descriptive using qualitative methods. The research was conducted at TK II PUTRI HIJAU Hospital KESDAM 1 / BB Medan for three months from March to May 2021. This study took samples in a presumptive way, namely by using the Non Random Sampling Technique with the accidental sampling technique method by collecting data through observation and interviews then the data was processed in thematic form. The results of the interview research obtained were 3 out of 5 respondents experienced drug withdrawal which was predominantly male (40%). the age of the late elderly (56-65 years) as much as (40%). The majority of occupations are self-employed (60%). And have suffered from diabetes from 6-10 years (60%). The fact of drug discontinuation is due to advanced age, occupation, and compliance with taking medication. The gender factor is very influential in the occurrence of diseases, especially DM, the female sex is more susceptible to Diabetes Mellitus because women have premenstrual syndrome after menapouse, but the results of the research obtained are predominantly male. Meanwhile, 2 female-dominant respondents did not drop out of medication but were less compliant in taking medication.